A Novel Loop: Mutual Regulation Between Epigenetic Modification and the Circadian Clock - Du, Shenxiu; Chen, Liang; Ge, Liangfa; Huang, Wei (Frontiers in Plant Science, 2019)
Due to periodic environmental fluctuations generated by the rotation of the earth, nearly all organisms have evolved an intrinsic timekeeper, the circadian clock, which can maintain rhythmic oscillations of 24 hours in biological processes and ultimately confer a fitness benefit. In the model plant Arabidopsis, the core mechanics of the circadian clock can be described as a complex regulatory network of three feedback loops composed of core oscillator genes. Transcriptional regulation of each oscillator gene is necessary to maintain the structure of the circadian clock. As a regulatory mechanism in gene transcription, epigenetic modification of chromatin affects the spatiotemporal expression of multiple genes. The accumulating evidence indicates that epigenetic modification is associated with circadian clock function in animals and plants. In addition, the rhythms of epigenetic modification have significant influence on the timing of molecular processes, including gene transcription. In this review, we summarize the recent progress of how histone acetylation, methylation and phosphorylation regulate the expression of the clock genes in Arabidopsis.